The EFFECT OF THE COMBINATION OF THE SESAME OIL AND VITAMIN E TO IMPROVE ERYTHROCYTE MEMBRANE ON HYPERCHOLESTEROL RATS - Jurnal, Badan Penerbitan (Asian Journal of Pharmaceutical Research and Development, 2019)
Objective: The purpose of this study was to determine the combination effect of sesame oil and vitamin E to the number of abnormal erythrocytes, and MDA levels by the amount of hemolysis. Hypercholesterolemia that is grown by erythrocyte membranes were decreased conditions that leads to atherosclerosis associated with oxidative stress which leads to lipid peroxidation. Sesame oil (SO) has special antioxidants that also contains 85% unsaturated fatty acid, where 40% consists of poly unsaturated fatty acid. Vitamin E is a chain breaker antioxidant that prevents the multiplication of free radical reactions in phospholipids. Methods: This research using 6 treatment groups, 3 groups received an atherogenic diet, while the other 3 groups received an atherogenic diet and treated with a combination of sesame oil with the same dose, added with 0.02 ml of vitamin E. Results: The results showed that the proportion of 1.2 ml SO and 0.02 ml of vitamin E, with the average amount (%) of hemolysis at 0.45% NaCl concentration was (5, 05 ±0.129), while in the control (33,87–1,919). The number (%) of erythrocytes is not normal (25,75± 2,473) while in the control (80,27± 4,631). Erythrocyte MDA level (0.229±0.039) µlmol / ml, while in the control (0.443 ± 0.013) µmol / ml. Conclussion: This research shows that the combination of oil and vitamin E had a significant decrease in the number of abnormal erythrocytes, the amount of hemolysis and MDA levels. The MDA reduction is followed by a decrease in the number of abnormal erythrocytes and the amount of hemolysis.